(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2020)
The article analyzes the paratextual structure that characterizes the collection dedicated to Calvino in Mondadori’s Oscar during the years of the first edition. Unlike the usual editorial practice of the collection – which accompanies the literary texts with critical writings by third voices – Opere di IC are presented by the author’s peritexts, reserving every space around Calvino’s texts for his voice. This is an exceptional case that is unmatched by any other Oscar’s section and which reflects Mondadori’s strategy of proposing to a general public the figure of a «classic» author who presents himself. The theoretical perspective of the work is based on Gérard Genette’s Paratexts and Roger Chartier’s The Order of Books, in which they illustrate how the editorial status contributes to influencing the reader’s reception of the text.